A Systematic Literature Review on Career Guidance through Thematic Learning in Early Childhood Education - Wiliya Novianti; Ririn Hunafa Lestari; Ifat Fatimah Zahro; Muhammad Rezza Septian (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
Thematic learning is a type of career guidance service that can be applied in early childhood education and is considered effective because its learning themes introduce various kinds of work. This study aims to analyze career guidance services for early childhood through the thematic learning process. The research employed the Systematic Literature Review (SLR) method by reviewing five research journal articles and two undergraduate theses accessible online. Data were collected using documentation techniques and analyzed using grounded theory with the Straussian approach. The findings indicate that career guidance services can be integrated into thematic learning in early childhood education through learning methods and media that are easy for teachers to understand and apply. This approach is particularly effective when implemented by educators with a bachelor’s degree in early childhood teacher education, as it helps address the limited involvement of guidance and counseling teachers in PAUD. Furthermore, integrating career guidance principles into thematic learning through systematic lesson planning allows the introduction of work-related concepts to children through themes relevant to their daily environment, fostering structured and focused career development from an early age.